The Relationship Between Stress Levels and Premenstrual Syndrome Incidents - Andi Muhammad Fadhyl Arsy; Arlina Wiyata Gama; Andi Irhamnia Sakinah; Azizah Nurdin; Zulfahmi Alwi (Journal La Medihealtico, 2025)
Adolescence is a formative stage marked by emotional instability and biological changes, creating a complex intersection between psychological and physiological development. In this context, premenstrual syndrome (PMS) is not merely hormonal but also a psychosomatic response to psychosocial stressors. This study examined the relationship between perceived stress and PMS among 256 female students from Madrasah Aliyah Negeri in Makassar, Indonesia. Using a quantitative cross-sectional design, data were collected with the Perceived Stress Scale (PSS-10) and the Shortened Premenstrual Assessment Form (SPAF). Statistical analysis using Chi-square and binary logistic regression revealed a strong association between PMS and stress (p = 0.000). The prevalence of PMS increased markedly with stress intensity, ranging from 6.7% among mildly stressed to 95.9% among severely stressed respondents. Stress emerged as a key predictor (AOR = 30.20 for moderate stress; AOR = 330.80 for severe stress), while adequate sleep and regular physical activity acted as protective factors. These findings suggest that adolescent stress manifests as embodied experiences influenced by educational and sociocultural expectations. In academically demanding and morally prescriptive environments, emotional distress often translates into somatic expressions. Thus, PMS may function as a covert form of communication an embodied narrative of unspoken emotional struggles. Effective management should therefore integrate stress reduction, menstrual health literacy, and emotional awareness, not only improving reproductive health but also validating adolescents’ psychosocial realities.